Protection of the Constitutional Rights of Workers Dismissed for Urgent Reasons According to Government Regulation Number 35 of 2021 - Sitorus, Ana Tince; Saliman, Abdul Rashid; Thamrin, Husni (International Journal of Science and Society, 2025)
This research delves into the alignment of regulations governing the Termination of Employment (PHK) due to grave misconduct, as outlined in Government Regulation No. 35 of 2021, with the principles safeguarding workers' constitutional rights enshrined in the 1945 Constitution (UUD 1945). Employer-initiated unilateral dismissals based on allegations of urgent violations, as specified in Article 52 paragraph (2) of PP 35/2021, pose a significant risk of contravening the tenets of due process and the right to legal safeguards guaranteed under Article 27 paragraph (2) and Article 28D paragraph (1) of the UUD 1945. This inquiry also draws on Constitutional Court Decision No. 012/PUU-I/2003, which underscored the necessity of judicial proceedings in termination cases linked to severe breaches, and Decision No. 91/PUU-XVIII/2020, which highlighted procedural deficiencies within the Job Creation Law. Employing a normative legal research methodology with an analytical lens, this study emphasizes legislative analysis and case law examination. Originality of this study lies in its finding that the application of unilateral termination of employment (PHK) without a court process can lead to injustice and harm workers who may lose their jobs without the opportunity to defend themselves. This research concludes that the provisions on urgent layoffs in PP 35/2021 should be reviewed to align with constitutional principles that offer fairer protection for workers. It is recommended that new employment regulations be created with a focus on balancing the protection of workers' rights with the interests of employers.